2011
DOI: 10.18043/ncm.72.5.351
|View full text |Cite
|
Sign up to set email alerts
|

School Nurses and Children With Diabetes: A Descriptive Study

Abstract: background Managing diabetes in children is complex. The aims of this descriptive study were to describe the care provided to children with diabetes by school nurses using case management, to identify differences in care on the basis of the workload of the nurse and the age of the child, to explore the role of the nurse in responding to emergencies, and to describe the relationship between case management and quality of life. methods School nurses completed an expanded health assessment. Individualized goals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Despite the rise in numbers of youth with T1D, research on school nursing and measurable diabetes outcomes in adolescents is scarce. Research on school nursing and students with T1D has focused on parental perspectives of safety and satisfaction in the school setting (Driscoll et al, 2015; Skelley et al, 2013), school nurse perspectives regarding diabetes management (Thorstensson, Fröden, Vikström, & Andersson, 2016; Wang & Volker, 2013), and case management (Engelke, Swanson, Guttu, Warren & Lovern, 2011; Peery, Engelke, & Swanson, 2012).…”
mentioning
confidence: 99%
“…Despite the rise in numbers of youth with T1D, research on school nursing and measurable diabetes outcomes in adolescents is scarce. Research on school nursing and students with T1D has focused on parental perspectives of safety and satisfaction in the school setting (Driscoll et al, 2015; Skelley et al, 2013), school nurse perspectives regarding diabetes management (Thorstensson, Fröden, Vikström, & Andersson, 2016; Wang & Volker, 2013), and case management (Engelke, Swanson, Guttu, Warren & Lovern, 2011; Peery, Engelke, & Swanson, 2012).…”
mentioning
confidence: 99%
“…Many studies have shown that school nurses can have a significant impact on improving diabetes care in children [1,[16][17][18]. When schools closed due to the quarantine, disadvantaged children were affected the most, due to lack of health care from school nurses and other factors [19].…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 Diabetes is a chronic illness that requires constant attention and monitoring. Parents and school nurses play a critical role in helping these children maintain control of their diabetes [1]. If diabetes control is not regulated during the childhood years, then these children are at risk of developing complications later in life [2].…”
Section: Introductionmentioning
confidence: 99%
“…Facilitators to forming a responsible and efficient school diabetes management team included competent school nurses, engaged parents of students with diabetes, responsible teachers, well-informed school leaders, adequate resources and professional support, and frequent and timely communication among stakeholders. More specifically, for school nurses, facilitators to the successful fulfillment of their responsibilities included adequate work experience (Bachman & Hsueh, 2008;Bobo et al, 2011;Darby, 2006;Engelke et al, 2011;Fisher, 2006;Izquierdo et al, 2009;Lineberry et al, 2018;March et al, 2020;Schwartz et al, 2010;, high confidence in performing care tasks (Berget et al, 2019;Fisher, 2006;Perfect & Jaramillo, 2012;Smith et al, 2012), higher education level (Bachman & Hsueh, 2008;Lineberry et al, 2018;March et al, 2020) reasonable workload (Engelke et al, 2011), sound decisions about assigning care tasks to nonmedical school personnel (Nimsgern & Camponeschi, 2005), differentiated care for younger and older students with diabetes (Nabors et al, 2005), and a close connection to the students' physicians (Radjenovic & Wallace, 2001). For parents of students with diabetes, regular school visits and educating classmates about diabetes were essential (Joshi et al, 2008).…”
Section: Facilitators Of School Diabetes Carementioning
confidence: 99%